Reflexivity, description and the analysis of social settings - Rodney Watson (Ciências Sociais Unisinos)
The concept of 'reflexivity' has become an often-intoned mantra in contemporary social science, particulary, perhaps, sociology. This article, however, argues that the 'blanket use' of 'reflexivity' glosses over and confuses many different actual definitions and understandings of the concept - not least because the concept operates differently as a move within each of the divergent analytic 'games' that compose the overall discipline. One (among many other) crucial distinctions is that between 'stipulative' and 'essential' reflexivity - the former originating in part in G.H.Mead's notions of the 'I' and the 'Me', and extended within current theories of reflexive modernity. This concept has been wrenched by professional social scientist from its mundane moorings and has been 'elevated' into an analytic technique of self interrogation. By contrast, 'essential' reflexivity, as adduced by ethnomethodological sociologists, remains resolutely emplaced in the domain of lay society-members' ordinary sense-making practices: it here refers to the reciprocal, back-and-forth determinations of sense of members' mundane descriptions of their specific circumstances and of the circumstances they describe - description and circumstance reflect upon each other during the sense-making practices. A brief example of essential reflexivity is given- reflexive formulations in ordinary conversations.